Effect of the charge interactions on the composition behavior of acrylamide/acrylic acid copolymerization in aqueous medium. (January 2018) - Fischer, Eric J.; Cuccato, Danilo; Storti, Giuseppe; Morbidelli, Massimo
Graphical abstract: Highlights: Acrylamide/acrylic acid copolymerization successfully monitored by in-situ 1 H NMR. Increase of Am/AA − concentration leads to larger reactivity of ionized monomer. At low concentration, this effect is purely diffusion-controlled. At high monomer concentration, reaction rate is mostly reaction controlled. Model successfully describes influence of ionic strength in both regimes. Abstract: Acrylamide and sodium acrylate are copolymerized in aqueous solution to study the influence of monomer concentration and ionic strength onto the reactivity ratios using in-situ 1 H NMR. Increasing the monomer content leads to larger reactivity of the ionized monomer. At low monomer concentration, this effect was reproduced by adding NaCl to increase the ionic strength, indicating that the reaction kinetics is largely governed by charge interactions. On the contrary, this was not observed at higher monomer content, suggesting that non-electrostatic effects are mainly responsible of the monomer concentration dependence at these conditions. A comprehensive mathematical model was developed to predict copolymer composition as a function of monomer concentration and ionic strength. It is based on a previously-proposed rate law of propagation for ionized monomers, which has been expanded to cover any ionization degree of acrylic acid. The model is capable to reproduce composition data from different sources obtained in a wide range of reaction conditions.